Application of soft systems in analysis of family and sexual violence, Pampas district - Marquez Camarena , Javier F (2021)
An analysis of family and sexual violence in the district of Pampas was made through the application of Soft Systems, a methodology that includes hard systems, which were clearly applied to technology (Checkland, 2000), being very inadequate to investigate systems large and complex organizational structures. The study area comprised the district of Pampas, where surveys and interviews were conducted with 360 people taken at random, the design of the structured problem on family and sexual violence was carried out considering the conceptual models of the mayor and the population, the model was built of confirmed and validated primary task based on said models obtained, whereit is appreciated that using a strategic plan and good education reduces violence. In summary, the application of Soft Systems positively influences the identification of alternatives to counteract family and sexual violence. With this methodology the activities and processes in the solution of the problem were identified; we can appreciate the education, security, talks and technological development which were involved in reducing violence. The starting point for structuring the aforementioned problem was coordination with the authorities of the Pampas district.